International Asset Pricing Models: The Case of ASEAN Stock Markets - Hooy, Chee-wooi; Goh, Kim-leng (Universiti Utara Malaysia, 2009)
This paper is about the role of economic grouping as it affects international capital asset pricing models, ICAPM.The conventional ICAPM is extended to include the economic grouping, regional and world factors.Inclusion of the economic grouping factor increases the explanatory power of the asset pricing models.Data on ASEAN (Indonesia, Malaysia, Philippines, Singapore and Thailand) stock markets are used in tests of the proposed models. The economic grouping factor turned out to be most important while the regional factor is least important for asset pricing in these stock markets. While four of the markets have higher systematic risk exposure to the economic group, the Singapore market, the largest market, exhibits higher exposure to world risk. The segmentation of emerging markets offers a possible explanation for these results.